Validitas Media Powerpoint Interaktif Kelas IV Sekolah Dasar - Ika Dewi Sukmawati; Dea Mustika (IJoIS: Indonesian Journal of Islamic Studies, 2021)
The purpose of this research is the validity of interactive powerpoint media for fourth grade elementary school. This research method uses development research with the ADDIE development model. This research was conducted in three stages, namely 1) the analysis stage consisted of educator analysis, student analysis and learning materials; 2) the design stage, namely the design of interactive powerpoint learning media using the powerpoint application; 3) the development stage, namely the process of making the design a reality. The results of this study indicate that interactive powerpoint media meet the very valid criteria. In learning 1 obtained an average result of 70.91% with a valid category which was declared suitable for use with revisions, then the researchers made several improvements so that in the second validation obtained a value of 90% with a very valid category, the interactive powerpoint learning media was feasible to use for learning process. In learning 4, the first validation value was obtained at 70.69% with a valid category and was declared suitable for use with revisions. Then the researchers made improvements according to the validator's suggestions so that in the second validation the average value was 92.11% with a very valid category level. Then the interactive powerpoint learning media in learning 4 is feasible to use for the learning process. So it can be concluded that the two learning media are feasible to use without revision with the category of validity reaching a very valid level by conducting a validation test twice.